Thermal Vibration of Thick Functionally Graded Material Spherical Shells by Using Third-order Shear Deformation Theory and Simply Homogeneous Equation - C.C. Hong (Computational Engineering and Physical Modeling)
The effect of third-order shear deformation theory (TSDT) on the functionally graded material (FGM) thick spherical shells under sinusoidal heating loads can be studied by using the generalized differential quadrature (GDQ) method. The TSDT of displacements is used to consider more shear effect than first-order shear deformation theory (FSDT) in thickness direction of thick materials. The stiffness in simpler form of thick FGM spherical shells and linear temperature rise can be studied in the thermo-elastic-stress-strain expressions. The thermal stress and displacement of dynamic vibrations for the FGM thick spherical shells can be computed and investigated. It is the novelty of purely thermal vibration studies by only using sinusoidal heating loads as applied heat flux on thick FGM spherical shell, and to verify the natural frequency effects of simply homogeneous equation and fully homogeneous equation, respectively on the displacements and stresses. The concrete results of the study are found for the dynamic values of center displacement in simply homogeneous equation case and underestimated to that fully homogeneous equation case at the corresponding time for thick FGM spherical shells.